DNA metabarcoding assays reveal a diverse prey assemblage for Mobula rays in the Bohol Sea, Philippines. Issue 5 (30th January 2019) - Bessey, Cindy; Jarman, Simon N.; Stat, Michael; Rohner, Christoph A.; Bunce, Michael; Koziol, Adam; Power, Matthew; Rambahiniarison, Joshua M.; Ponzo, Alessandro; Richardson, Anthony J.; Berry, Oliver
Abstract: Diet studies provide base understanding of trophic structure and are a valuable initial step for many fields of marine ecology, including conservation and fisheries biology. Considerable complexity in marine trophic structure can exist due to the presence of highly mobile species with long life spans. Mobula rays are highly mobile, large, planktivorous elasmobranchs that are frequently caught either directly or as bycatch in fisheries, which, combined with their conservative life history strategy, makes their populations susceptible to decline in intensely fished regions. Effective management of these iconic and vulnerable species requires an understanding of the diets that sustain them, which can be difficult to determine using conventional sampling methods. We use three DNA metabarcode assays to identify 44 distinct taxa from the stomachs ( n = 101) of four sympatric Mobula ray species ( Mobula birostris, Mobula tarapacana, Mobula japanica, and Mobula thurstoni ) caught over 3 years (2013–2015) in a direct fishery off Bohol in the Philippines. The diversity and incidence of bony fishes observed in ray diets were unprecedented. Nevertheless, rays showed dietary overlap, with krill ( Euphausia ) dominating their diet. Our results provide a more detailed assessment of sympatric ray diets than was previously described and reveal the complexity that can exist in food webs at critical foraging habitats. Abstract : We use three DNA metabarcode assays to identify 44 distinct taxa from the stomachs ( n = 101) of four sympatric Mobula ray species ( Mobula birostris, Mobula tarapacana, Mobula japanica, and Mobula thurstoni ) caught over 3 years (2013–2015) in a direct fishery near Bohol in the Philippines. The diversity and incidence of bony fishes observed in ray diets were unprecedented. Nevertheless, rays showed dietary overlap, with krill ( Euphausia ) dominating their diet.